Pengaruh Pola Asuh Demokratis Terhadap Pemenuhan Gizi Melalui Pemberian Bekal Makanan Anak Usia Dini Kelompok B Usia 5-6 Tahun - Melinda Karim; Irvin Novita Arifin; Yenti Juniarti (Fakultas Ilmu Pendidikan Universitas Negeri Gorontalo, 2023)
This study aims to determine the influence of democratic parenting styles on nutrition fulfillment through lunch box provision for early childhood Group B aged 5-6 years. This Expost Facto research was conducted on a population of 40 children, with a sample of 17 children. Data were collected through observation and questionnaires. Based on the data analysis result, the value